Biological characterization of the skin of shortfin mako shark Isurus oxyrinchus and preliminary study of the hydrodynamic behaviour through computational fluid dynamics. Issue 1 (5th June 2015) - Díez, G.; Soto, M.; Blanco, J. M.
<x xml:space="preserve">Abstract</x> This study characterized the morphology, density and orientation of the dermal denticles along the body of a shortfin mako shark Isurus oxyrinchus and identified the hydrodynamic parameters of its body through a computational fluid‐dynamics model. The study showed a great variability in the morphology, size, shape, orientation and density of dermal denticles along the body of I. oxyrinchus. There was a significant higher density in dorsal and ventral areas of the body and their highest angular deviations were found in the lower part of the mouth and in the areas between the pre‐caudal pit and the second dorsal and pelvic fins. A detailed three‐dimensional geometry from a scanned body of a shark was carried out to evaluate the hydrodynamic properties such as drag coefficient, lift coefficient and superficial (skin) friction coefficient of the skin together with flow velocity field, according to different roughness coefficients simulating the effect of the dermal denticles. This preliminary approach contributed to detailed information of the denticle interactions. As the height of the denticles was increased, flow velocity and the effect of lift decreased whereas drag increased. The highest peaks of skin friction coefficient were observed around the pectoral fins.